MEDICAL CARE CHARGE AND OUTCOMES IN HYPERTENSIVE PATIENTS REFERED FROM HOSPITAL TO DISTRICT HEALTH PROMOTION HOSPITAL OF SAMCHUK DISTRICT, SUPHANBURI PROVINCE - Wongpornpipat, Poolsak; Upakdee, Nilawan (Thai Bulletin of Pharmaceutical Sciences, 2018)
The objectives of this research were to compare medical care charge and outcomes in hypertensive patients at district health promotion hospital. This was a descriptive study collected data by using medical history report from HOSxP of Samchuk hospital and HOSxP PCU of district health promotion hospital at Samchuk, Suphanburi in fiscal year 2014 and 2015, respectively. The economic and clinical outcomes of hypertensive patients during treatment at Samchuk Hospital were compared with treatment at the district health promotion hospital. The results in 411 patients found that most of patients were female (67.9%). An average age was 64.2 ± 10.1 years and most of patients have elderly universal coverage insurance (65.5%). Mean of medicine charge at hospital was not different from mean of medicine charge of the district health promotion hospital. Clinical outcomes of blood pressure value found that mean difference significantly in blood pressure both systolic (p-value = 0.25) and diastolic (p-value < 0.05)